Coronavirus Disease 2019 and Cash Flow: Sebuah Studi Kualitatif - Yopi Yudha Utama; Nadya Arisanti (Jurnal Akuntansi Terapan dan Bisnis, 2021)
Coronavirus disease 2019 or known as covid-19 has an impact on various sectors. Besides the health sector, one of the sectors most affected is the economic or financial sector. This can be seen from a number of business actors who close their businesses, including the SME business. This research was conducted to find out how some SMEs managing cash flow to maintain their businesses during the pandemic, especially SME. Therefore, this research was conducted using a case study approach with data collection techniques in the form of interviews with several SMEs. The informants selected in this study came from various business sectors. Among them in the field of bag production, convection, to the food sector. Most of the informants in this study experienced the effects of the co-19 pandemic. Some policies were decided by the informant. These policies such as reimbursement of fixed costs to variable costs, then change the focus of the business, then look for relationships in the immediate area, this policy is taken as a step to keep maintaining the business and amid uncertain conditions. Keywords: Covid-19, Cash Flow, SME, Policy